2012
DOI: 10.1007/s11095-012-0829-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Yew Tree Tubulin and a Comparison of its Interaction with Paclitaxel to Human Tubulin

Abstract: The yew has achieved a significant reduction of paclitaxel's affinity for its tubulin by utilizing several specific residue changes in the binding pocket for paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Interesting research was reported on the poor affinity of paclitaxel to tubulin derived from the yew tree (Taxus baccata), which is a producer of this cytotoxin. The analysis indicated that the paclitaxel-binding site of yew tree tubulin contains several amino acid substitutions compared to human tubulin, all of which reduce the binding affinity of paclitaxel to yew tree tubulin [112].…”
Section: Molecular Modeling and Virtual Screeningmentioning
confidence: 99%
“…Interesting research was reported on the poor affinity of paclitaxel to tubulin derived from the yew tree (Taxus baccata), which is a producer of this cytotoxin. The analysis indicated that the paclitaxel-binding site of yew tree tubulin contains several amino acid substitutions compared to human tubulin, all of which reduce the binding affinity of paclitaxel to yew tree tubulin [112].…”
Section: Molecular Modeling and Virtual Screeningmentioning
confidence: 99%
“…The plant alpha tubulin sequences, including that cloned from T. cuspidata in this study and that cloned from T. baccata by Tuszynski et al 24) , were aligned with that of human alpha tubulin cloned from HEK293T embryonic kidney cells in this study (Fig. S1).…”
Section: Resultsmentioning
confidence: 98%
“…The amino acid sequences of plant beta or beta-1 tubulins from H. sapiens (NP_821133.1), T. cuspidata (cloned in this study), T. baccata (WWSSB1), 24) A. thaliana (BAB10059.1), Eucalyptus grandis (ABS50665.1), G. max (NP_001239638), Gossypium hirsutum (AF487511_1), Lupinus albus (CAA49736), O. sativa (AAA66495.1), T. aestivum (AAD10487.1), and Vanilla planifolia (ADZ76155.1) were aligned using Clustal X (Fig. S2).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…With this limitation, molecular modelling and computer simulations can offer a comprehensive and alternative approach to understand these interactions [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Although there have been previous attempts to model the hPD-1/hPD-L1 and hPD-1/hPD-L2 complexes, none of these models correlated well with available experimental data.…”
Section: Research Highlightmentioning
confidence: 99%